Next-Generation Sequencing of the Microbial Community Profile In Free-Range Chicken (Gallus gallus domesticus) Cecum from East Nusa Tenggara Province: Microbial community profile in free-range chicken (Gallus gallus domesticus) cecum - Eufrasia Reneilda Arianti Lengur; Yoga Dwi Jatmiko; Endang Arisoesilaningsih; Eko Widodo (Journal of Tropical Life Science, 2023)
Free-range chicken is livestock reared to support the humans' need for protein alongside its ritualistic use in traditional medicine to treat diseases. This study investigates the diversity of bacterial communities in the free-range chicken cecum reared in different East Nusa Tenggara Province localities comprising Sambi 1, Sambi 2 villages, Labuan Bajo, and Kupang City. The extracted chromosomal DNA was subjected to next-generation sequencing using the V3-V4 region primers. Results revealed that the Kupang chicken cecum had the highest total tags, while the Sambi 2 village recorded the lowest. Similarly, Sambi 2 chicken cecum exhibited the highest unique tags (6662) and OTUs number (1261), while the Kupang samples gave the lowest at 2550 and 745, respectively. The Shannon diversity index for bacterial diversity demonstrated that cecum samples from Labuan Bajo (5.679) were more diverse than Sambi 1 (5.378), Sambi 2 (5.653), and Kupang samples (3.77). The bacteria with the highest dominance index (0.935) was found in Sambi 2, while the lowest was observed in the Kupang samples (0.082). The three bacterial phyla showing the highest relative abundance were those from Sambi 1, Sambi 2, and Labuan Bajo cecum samples, comprising Firmicutes, Bacteroidota, and Actinobacteriota.Conversely, the Kupang samples showed an abundance of Firmicutes, Bacteroidota, and Campilobacterota, compared to the Lactobacillus-dominated Kupang, Sambi 1, and Sambi 2 chicken cecum samples. The highest relative abundance for Bifidobacterium occurred in Sambi 1 and Sambi 2 chicken cecum samples, the Kupang samples were Campylobacter dominated, and Olsenella was abundant in the Labuan Bajo samples. Intriguingly, the bacterial composition in the tested chicken cecum samples largely comprised beneficial bacteria such as the lactic acid bacteria group. This bacterial group can be further characterized for obtaining probiotic cultures that could improve the health of free-range chickens.